2014
DOI: 10.14692/jfi.10.6.210
|View full text |Cite
|
Sign up to set email alerts
|

Penyakit Kerupuk Tembakau di Sumatera Barat

Abstract: ABSTRAKPenyakit daun keriting (kerupuk) merupakan penyakit baru pada tanaman tembakau di Sumatera Barat. Penyakit ini sudah tersebar di seluruh area pertanaman tembakau di Kabupaten Limapuluh Kota dengan intensitas serangan 2.5-26.3%. Hasil amplifikasi dengan metode polymerase chain reaction menggunakan primer universal Begomovirus PAL1v 1978/PAR1c 715 dari daun tanaman tembakau yang bergejala menghasilkan amplikon berukuran 1600 pb. Hasil ini mengindikasikan adanya infeksi Begomovirus. Analisis urutan DNA iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Trisno et al (2010) menambahkan infeksi pada cabai besar dapat menimbulkan kerugian 60 -80%. Selain menginfeksi cabai, PYLCV juga dapat menyerang tanaman tomat (Lycopersicum esculentum) (Aidawati at al., 2005;Santoso et al, 2008), Nicotiana tabacum (Hidayat et al, 2008;Trisno et al, 2014)), gulma (Ageratum conyzoides), N. bentamiana (Sudiono et al, 2001;Sukamto et al, 2005), dan kedelai (Glycine max) (Sutrawati et al, 2020).…”
Section: Pendahuluanunclassified
“…Trisno et al (2010) menambahkan infeksi pada cabai besar dapat menimbulkan kerugian 60 -80%. Selain menginfeksi cabai, PYLCV juga dapat menyerang tanaman tomat (Lycopersicum esculentum) (Aidawati at al., 2005;Santoso et al, 2008), Nicotiana tabacum (Hidayat et al, 2008;Trisno et al, 2014)), gulma (Ageratum conyzoides), N. bentamiana (Sudiono et al, 2001;Sukamto et al, 2005), dan kedelai (Glycine max) (Sutrawati et al, 2020).…”
Section: Pendahuluanunclassified
“…The latest confirmation towards leaf curl tobacco sample from Klaten was also caused by TYLCV-Kanchanaburi (Natsuaki et al, 2015;personal communication). Trisno et al (2014) reported that leaf curl disease at West Sumatera was caused by Pepper yellow leafcurl Indonesia virus (PYLCIndV). While Hidayat et al (2008) reported the leaf curl disease at Jember, East Java was caused by Tobacco leaf curl virus (ToLCV).…”
Section: Identification Of Disease Caused Agent In Laboratorymentioning
confidence: 99%
“…It was caused by TLCV of Begomovirus genus (Hidayat et al, 2008), followed by the report of Aji (2012) who stated that the leafcurl disease on tobacco at Klaten, Central Java was caused by Tomato yellow leafcurl virus (TYLCV). Recently, Trisno et al (2014) reported the leafcurl disease was also happened in West Sumatera, which was caused by Pepper yellow leafcurl Indonesia virus (PYLIndV). Vorstenlanden tobacco is a new host of Begomovirus which previously there are some reports regarding epidemic of yellow leaf curl on chili and tomato in Central Java (Sulandari et al, 2001;Sumardiyono et al, 2003;Hartono, 2008).…”
Section: Introductionmentioning
confidence: 99%